2014
DOI: 10.1007/s00345-014-1418-y
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor muscle function is an independent predictor of outcome after retrourethral transobturator male sling procedure

Abstract: PFMF improved significantly after RTS procedure. Higher muscle fatigue and weak PFMF were independent predictors of RTS failure. Digital rectal evaluation of PFMF is a simple and reliable clinical tool, which can be used by urologists in daily routine to predict the RTS outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Until now, the studies did not prove significant progressive effectiveness in favor of the AdVance XP sling. Nevertheless, it emphasized advan-tages, for example, in the decrease of failure frequency in overweight participants [27,28]. A study comparing patients treated with either the AdVance sling or the Ad-Vance XP sling revealed a total cure rate of 77% following a median follow-up of 49 months [20,29].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the studies did not prove significant progressive effectiveness in favor of the AdVance XP sling. Nevertheless, it emphasized advan-tages, for example, in the decrease of failure frequency in overweight participants [27,28]. A study comparing patients treated with either the AdVance sling or the Ad-Vance XP sling revealed a total cure rate of 77% following a median follow-up of 49 months [20,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, the ICIQ-UI SF and OABSS will also be used as subjective measures to investigate UI symptoms and QoL. The status of pelvic floor muscles is closely related to urinary incontinence symptoms, and its electrical activity is widely used to reflect objective muscle contraction abilities [ 12 , 40 ]. Thus, both subjective and objective data regarding bladder function and QoL will be collected using self-reported questionnaires.…”
Section: Discussionmentioning
confidence: 99%
“…A probe will be inserted into the correct place of the vaginal (for females) or rectal (for males) region, and the PFM activity at rest will be recorded for 30 s, followed by two 5-s maximum voluntary contractions (MVCs) with a break of 15 s in between. The sEMG activity onset threshold will be considered the mean plus two standard deviations of the filtered and rectified EMG during the 30 s rest according to Baur et al [ 40 ]. The sEMG outcomes will be calculated as root mean square (RMS) values within the respective time intervals and averaged over 10 s.…”
Section: Methodsmentioning
confidence: 99%
“…From those findings, PFM functions can be measured by using the manometer positioned in healthy men. Although previous studies have assessed PFM strength with a manometer or the Oxford scale after prostatectomy, 18,19 to the best of our knowledge, the reliability of PFM function assessments in men has not been addressed. The present study showed that manometry is a reliable tool to evaluate PFM function in healthy men.…”
Section: Discussionmentioning
confidence: 99%